A nature-based solution to reduce soil water vertical leakage in arid sandy land - Liu, Wei-Feng; Huang, Ze; Guo, Zhengxiong; López-Vicente, Manuel; Wang, Zhanjun; Wu, Gao-Lin (Geoderma, 2023)
•Blocking effects of Pisha sandstone on water leakage in sandy land were examined.•Inserted Pisha sandstone in sandy land changed the vertical distribution of soil water.•Inserted Pisha sandstone at 10–15 cm depth caused high permeability resistance.•Inserted Pisha sandstone effectively hindered the downward leakage of sandy soil water. Quick water seepage in sandy soils results in a serious restriction for ecological restoration, becoming a worldwide urgent research issue in arid areas. Search for practical solutions are focused on reserving the limited rainfall into topsoil layer to meet plant water demand. Based on fieldwork, this study evaluates the blocking effects of Pisha sandstone on soil water leakage, by inserting sandstone layers in the different soil depths (10–15 cm, 20–25 cm, 30–35 cm), which act as isolation layers within the sandy soil. Results showed that the inserted Pisha sandstone layers significantly decreased the soil water infiltration rates at the different stages and cumulative infiltration. The inserted sandstone layer at the depth of 10–15 cm presented the highest permeability resistance, and its initial infiltration rate, stable infiltration rate and average infiltration rate decreased by 102.42 mm h−1, 144.30 mm h−1 and 132.79 mm h−1, respectively. Meanwhile, the soil water content in the 5–10, 20–25, and 30–35 cm soil layers increased by 2.17%, 2.20%, and 1.37%, respectively, due to the inserted Pisha sandstones. This experimental study proves that the insertion of Pisha sandstones effectively hinders the downward penetration of soil water in sandy soil. These findings provide a new alternative for an effective solution of the fast water leakage problem of sandy land.